Kijing Taiwan Flour Subtitution in 3-5 cm Tilapia Fish Feed Frmulation (Substusi Tepung Kijing Taiwan Dalam Formulasi Pakan Ikan Nila Ukuran 3-5 cm) - Saiful, Nurrahmi Iriani; Lumenta, Cyska; Sampekalo, Julius (Universitas Sam Ratulangi, 2015)
The research was conducted in the Nutrition and Fish Feed Technology Laboratory. Breeding container used is 15 units of Aquarium and each container stocked with 10 fishes at size 3-5 cm. The objectives of this research is: to determine the effect of feeding with different composition of Kijing Taiwan flour to the Relative growth of tilapia fish and to determine which Kijing Taiwan feed composition that has the best feed efficiency value for tilapia. The research design used was a Completely Randomized Design (CRD) using five (5) different treatments and three (3) repetitions. Where Treatment A (0% without flour Kijing Taiwan), treatment B (10% flour Kijing Taiwan), treatment C (20% flour Kijing Taiwan), treatment D (30% flour Kijing Taiwan) and treatment E (40% flour Kijing Taiwan ). The frequency of feeding was 3 times a day with a weight of 5% from the fish total weight. An observation of growth was done once a week. The analysis results of the five treatments applied, showed that the relative growth value during the research for Treatment E contribute (387.62%), followed by treatment D (268.57%), treatment C (202.86%), treatment B (182, 86%) and treatment A (131.43%). Meanwhile for the Feed Efficiency Value in treatment E contribute (48.73%) followed by treatment B (40.14%), treatment C (37.03%), treatment D (36.70%) and treatment A (28.91%). It can be concluded that the feed with additional 40% of Kijing Taiwan flour provide better relative growth and better feed efficiency value than any other feeds. Â Keywords: Substitution, flour Kijing Taiwan, relative growth, feed efficiency and tilapia